2016
DOI: 10.3390/ma9060468
|View full text |Cite
|
Sign up to set email alerts
|

Microbially Induced Calcite Precipitation Employing Environmental Isolates

Abstract: In this study, five microbes were employed to precipitate calcite in cohesionless soils. Four microbes were selected from calcite-precipitating microbes isolated from calcareous sand and limestone cave soils, with Sporosarcina pasteurii ATCC 11859 (standard strain) used as a control. Urease activities of the four microbes were higher than that of S. pasteurii. The microbes and urea–CaCl2 medium were injected at least four times into cohesionless soils of two different relative densities (60% and 80%), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 26 publications
(30 reference statements)
1
14
1
Order By: Relevance
“…Although most of the other studies identified Sporosarcina as rare Firmicutes in the cave environment [38], our study identified 46.15% of Sporosarcina. In agreement with our study, a study by Kim et al [38] has revealed two bacterial isolates, Sporosarcina globispora and Sporosarcina spp., from limestone cave soil samples that play crucial roles in calcite precipitation in the cave soil. Bacillus (15.38%) has also been observed as one of the genus in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…Although most of the other studies identified Sporosarcina as rare Firmicutes in the cave environment [38], our study identified 46.15% of Sporosarcina. In agreement with our study, a study by Kim et al [38] has revealed two bacterial isolates, Sporosarcina globispora and Sporosarcina spp., from limestone cave soil samples that play crucial roles in calcite precipitation in the cave soil. Bacillus (15.38%) has also been observed as one of the genus in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…B. cereus isolated from soil and marine environment are known to hydrolyse urea. 9,17,27,28 Similarly, B. licheniformis is also involved to precipitate calcium carbonate by ureolysis. 16 All the species that tested positive for ureolytic activity could grow on urea as sole carbon and nitrogen source consistently.…”
Section: Discussionmentioning
confidence: 99%
“…15 Bacillus is the most common genus of bacteria known to perform biomineralization by implementing ureolytic activities. Some specic species are B. sphaericus, 7 B. lentus, 17 B. pasteurii 30 and B. licheniformis. 16 Bacteria involved in biomineralization are important in stabilizing soil, especially in regions and cities with windy and desert-like conditions such as in the Gulf region.…”
Section: Introductionmentioning
confidence: 99%
“…The cementation reagent is composed of 20 g urea, 10 g NH 4 Cl, 3 g nutrient broth, 2.8 g CaCl 2 and 2.12 g NaHCO 3 per liter of de-ionized water reported in several studies (e.g., [4,12,23,38,63,69,71,72]. In all the studies cited, 3 g/l of nutrient broth was added to the cementation reagent because it was the most viable amount for survival of bacteria [66].…”
Section: Cementation Reagentmentioning
confidence: 99%